Relationship between photosynthetic pigments and corn production under nitrogen sources - Ezequiel Zibetti Fornari (Pesquisa Agropecuária Tropical, 2020)
Nitrogen (N) is a dynamic element in the soil, so new nitrogen fertilization alternatives are required as a way of maximizing its efficiency. Besides, vegetation sensors are a way to assess and manage the nutritional demands of plants. This study aimed to evaluate the effect of nitrogen sources on photosynthetic pigments and their correlation with corn grain yield and dry biomass. The experiment was carried out in a randomized block design with nitrogen sources (mineral, organic and biological). Contents of chlorophyll a, b and total, as well as carotenoids, were evaluated. The chlorophyll indices evaluated by both methods were positively correlated with each other and with the grain yield per plant. Nitrogen fertilization 100 % mineral was superior, when compared to the other treatments, with increments of up to 44 %. There was a positive relationship between the methods of determining and estimating the chlorophyll contents. The grain yield per plant showed the highest values when using the 100 % mineral fertilizer source, with increments above 10 %, in relation to the other sources, spending US$ 89.77 on fertilizer and earning over US$ 538.60 on grain yield. There was a positive correlation between the photosynthetic pigments obtained by both methods and grain yield per plant. Both methods are recommended for the evaluation of chlorophyll concentrations.